2004
DOI: 10.3201/eid1002.030452
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of SARS among Medical Students Exposed to Single Patient, Hong Kong

Abstract: We studied transmission patterns of severe acute respiratory syndrome (SARS) among medical students exposed exclusively to the first SARS patient in the Prince of Wales Hospital in Hong Kong, before his illness was recognized. We conducted a retrospective cohort study of 66 medical students who visited the index patient’s ward, including 16 students with SARS and 50 healthy students. The risk of contracting SARS was sevenfold greater among students who definitely visited the index case’s cubicle than in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
243
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(261 citation statements)
references
References 14 publications
2
243
0
10
Order By: Relevance
“…Previous cases have shown that medical students, especially the pre-clinical year medical students, are at high risk of newly emerging diseases, including SARS and swine flu. 16,17 Our results revealed that health colleges' students had a good level of awareness of the clinical aspects of MERS, especially the mode of transmission and prevention. This result was in consistent with the previous studies in other parts of Saudi Arabia which indicated that general Saudi population, health care worker as well as medical students showed a high level of awareness in the clinical aspect of the disease.…”
Section: Discussionmentioning
confidence: 69%
“…Previous cases have shown that medical students, especially the pre-clinical year medical students, are at high risk of newly emerging diseases, including SARS and swine flu. 16,17 Our results revealed that health colleges' students had a good level of awareness of the clinical aspects of MERS, especially the mode of transmission and prevention. This result was in consistent with the previous studies in other parts of Saudi Arabia which indicated that general Saudi population, health care worker as well as medical students showed a high level of awareness in the clinical aspect of the disease.…”
Section: Discussionmentioning
confidence: 69%
“…It has been proposed that the severe acute respiratory syndrome (SARS) outbreak in the Hong Kong M Hotel was due to contaminated environmental surfaces [8], and that those in Amoy Garden in Hong Kong, in airplanes, and in the Prince of Wales Hospital in Hong Kong were due to airborne transmission [9][10][11]. Roy and Milton have suggested that SARS-CoV is not transmitted by either droplet transmission or airborne transmission, but rather by a process lying somewhere between the two [12].…”
Section: Discussionmentioning
confidence: 99%
“…112,113 Since publication of the 2003 Infection Control Guideline for CF, several studies conducted in people with and without CF who are infected with viral or bacterial pathogens have expanded our understanding of droplet transmission and now challenge the 3-foot rule. These studies include epidemiologic data collected during outbreaks of influenza 114,115 and SARS in non-CF individuals, [116][117][118] experimental and observational studies performed in people with CF, [119][120][121] and studies of the dynamics of infectious aerosols. 119,122,123 …”
Section: Iia Contact and Droplet Transmissionmentioning
confidence: 99%
“…Infectious droplets containing influenza virus and SARS-CoV traveled 3-6 feet. 6,114,116,118 Aerosols of droplet nuclei from patients infected with influenza can be generated during intubation and suctioning. Droplet size and distance traveled can be affected by (1) environmental factors (eg, humidity, temperature, air currents, and number of air changes per hour in a room), (2) agent factors (eg, infectious load, transferability, survivability, infectivity, and contagiousness), and (3) host factors (eg, susceptibility and behavior).…”
Section: Iic Emerging View Of Droplet Transmissionmentioning
confidence: 99%